Employee engagement as a moderator between customer value proposition and company performance during COVID-19 - Zhu Zining; Charles Ramendran SPR; Wong Lai Soon (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2023)
The COVID-19 pandemic has crippled and caused varying degrees of damage to most industries since early 2020. Many Chinese companies, particularly SMEs, are on the verge of bankruptcy due to their vulnerability when facing business losses. Employee stress has been increasing due to increased work and retrenchment stress. The stress on the employee has then reduced their motivation and engagement and thus affected their performance. Reviews of the pertinent literature show that there is a need to study the moderating effect of employee engagement on the relationship between customer value proposition and company performance, which is the purpose of this study. This study employs a structured questionnaire to collect data through an online survey method from targeted Chinese SMEs. From the collected data, 109 usable data have been analyzed using covariance-based SEM via SPSS and AMOS software. The findings of this study show that the customer value proposition has a significant positive effect on company performance and that employee engagement moderates the relationship between the customer value proposition and company performance in a positive manner, though marginally. The moderate effect of employee engagement on the relationship between the customer value proposition and company performance is contributing in the relevant literature. The results of this study suggest to industrial practitioners that they should focus not only on customers but also on the wellbeing of internal employees in order to grow their business.